2019
DOI: 10.1063/1.5085302
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity comparison of absorption and grating-based phase tomography of paraffin-embedded human brain tissue

Abstract: Advances in high-resolution hard X-ray computed tomography have led to the field of virtual histology to complement histopathological analyses. Phase-contrast modalities have been favored because, for soft tissues, the real part of the refractive index is orders of magnitude greater than the imaginary part. Nevertheless, absorption-contrast measurements of paraffin-embedded tissues have provided exceptionally high contrast combined with a submicron resolution. In this work, we present a quantitative comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
2

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Combination of these two contrast modes is very useful when the sample has multiple phases, for example highly absorbing components combined with slightly absorbing or purely phase-sensitive materials. [1][2][3][4][5] The third contrast mode that we can obtain from XGTI is the Small Angle X-ray Scattering (SAXS) contrast which manifests itself as reduced visibility of the interference pattern due to presence of the sample. It gives access to spatial information below the pixel size of the detector.…”
Section: Introductionmentioning
confidence: 99%
“…Combination of these two contrast modes is very useful when the sample has multiple phases, for example highly absorbing components combined with slightly absorbing or purely phase-sensitive materials. [1][2][3][4][5] The third contrast mode that we can obtain from XGTI is the Small Angle X-ray Scattering (SAXS) contrast which manifests itself as reduced visibility of the interference pattern due to presence of the sample. It gives access to spatial information below the pixel size of the detector.…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be noted that the scans were not adapted to absorption imaging. Excellent results have been obtained for imaging of paraffin-embedded brain tissue with absorption-based microCT using optimised setups at synchrotron and also laboratory X-ray sources [Khimchenko et al, 2016a,b;Bikis et al, 2019]. On the other hand, it has been shown that for brain specimens scanned in formalin the phase-contrast signal is nonetheless superior to the absorption image [Schulz et al, 2010].…”
Section: Discussionmentioning
confidence: 99%
“…Many experiments are carried out with the in-line phase contrast geometry, but apply also to other techniques. For increased sensitivity the (single-) grating interferometry setup is used [19][20][21][22][23][24] , which is compatible not only with the energy bandwidth provided by the multilayer monochromator but also in pink beam mode 10,11 . Grating interferometry provides in addition phase and small angle scattering information.…”
Section: Operando Imagingmentioning
confidence: 99%